Baicalin Inhibits IL-17-Mediated Joint Inflammation in Murine Adjuvant-Induced Arthritis - Xue Yang; Ji Yang; Hejian Zou (Clinical and Developmental Immunology)
T-helper-17 (Th17) cells are implicated in a number of inflammatory disorders including rheumatoid arthritis. Antagonism of Th17 cells is a treatment option for arthritis. Here, we report that Baicalin, a compound isolated from the Chinese herb Huangqin (Scutellaria baicalensis Georgi), relieved ankle swelling and protected the joint against inflammatory destruction in a murine adjuvant-induced arthritis model. Baicalin inhibited splenic Th17 cell population expansion in vivo. Baicalin prevented interleukin- (IL-) 17-mediated lymphocyte adhesion to cultured synoviocytes. Baicalin also blocked IL-17-induced intercellular adhesion molecule 1, vascular cell adhesion molecule 1, IL-6, and tumor necrosis factor-alpha mRNA expression in cultured synoviocytes. Collectively, these findings suggest that Baicalin downregulates the joint inflammation caused by IL-17, which is likely produced by an expanded population of splenic Th17 cells in experimental arthritis. Baicalin might be a promising novel therapeutic agent for treating rheumatoid arthritis in humans.